Surgical stabilization of rib fractures in octogenarians and beyond—what are the outcomes?. Issue 6 (June 2021) - Pieracci, Fredric M.; Leasia, Kiara; Hernandez, Matthew C.; Kim, Brian; Cantrell, Emily; Bauman, Zachary; Gardner, Scott; Majercik, Sarah; White, Thomas; Dieffenbaugher, Sean; Eriksson, Evert; Barns, Matthew; et al.
Abstract : BACKGROUND: Prospective studies of surgical stabilization of rib fractures (SSRF) have excluded elderly patients, and no study has exclusively addressed the ≥80-year-old subgroup. We hypothesized that SSRF is associated with decreased mortality in trauma patients 80 years or older. METHODS: Multicenter retrospective cohort study involving eight centers. Patients who underwent SSRF from 2015 to 2020 were matched to controls by study center, age, injury severity score, and presence of intracranial hemorrhage. Patients with chest Abbreviated Injury Scale score less than 3, head Abbreviated Injury Scale score greater than 2, death within 24 hours, and desire for no escalation of care were excluded. A subgroup analysis compared early (0–2 days postinjury) to late (3–7 days postinjury) SSRF. Poisson regression accounting for clustered data by center calculated the relative risk (RR) of the primary outcome of mortality for SSRF versus nonoperative management. RESULTS: Of 360 patients, 133 (36.9%) underwent SSRF. Compared with nonoperative patients, SSRF patients were more severely injured and more likely to receive locoregional analgesia. There were 31 hospital deaths among the entire sample (8.6%). Multivariable regression demonstrated a decreased risk of mortality for the SSRF group, as compared with the nonoperative group (RR, 0.41; 95% confidence interval, 0.24–0.69; p < 0.01). However, SSRF patients were more likely to develop pneumonia, and had an increased duration of both mechanical ventilation and intensive care unit stay. There were no differences in discharge destination, although the SSRF group was less likely to be discharged on narcotics (RR, 0.66; 95% confidence interval, 0.48–0.90; p = 0.01). There was no difference in adjusted mortality between the early and late SSRF subgroups. CONCLUSION: Patients selected for SSRF were substantially more injured versus those managed nonoperatively. Despite this, SSRF was independently associated with decreased mortality. With careful patient selection, SSRF may be considered a viable treatment option in octogenarian/nonagenarians. LEVEL OF EVIDENCE: Therapeutic, Level IV Abstract : Supplemental digital content is available in the text.